Luteal-phase ovarian stimulation is a feasible method for poor ovarian responders undergoing in vitro fertilization/intracytoplasmic sperm injection-embryo transfer treatment compared to a GnRH antagonist protocol: A retrospective study - Li-Hong Wei; Wen-Hong Ma; Ni Tang; Ji-Hong Wei (Elsevier, 2016)
Objective: Poor ovarian response to ovarian hyperstimulation is one of the biggest challenges in assisted reproduction technology. Although many stimulation protocols have been established to improve clinical outcomes in poor ovarian responders (PORs), which protocol is the most effective remains controversial. Luteal-phase ovarian stimulation (LPOS) has been used in normal ovarian responders with satisfactory outcomes. However, the efficacy of LPOS in PORs is unclear. This study aimed to compare the efficacy of LPOS and GnRH antagonist (GnRH-ant) in PORs. Materials and methods: The clinical parameters in PORs who received LPOS (50 cycles in 39 patients) or GnRH-ant (158 cycles in 123 patients) were compared. Results: Compared with those in the GnRH-ant group, the PORs in the LPOS group showed significantly fewer basal antral follicles (3.1 ± 2.2 vs. 4.1 ± 1.6, p < 0.001) and a higher in vitro fertilization rate. There were no significant differences in the numbers of retrieved oocytes and D3 transferable embryos between the two groups. However, the pregnancy rate in the LPOS group (46.4%) was significantly higher than that in the GnRH-ant group (25.8% overall; 22.9% from fresh embryos and 29.6% from frozen embryos). Moreover, 23 PORs in the LPOS group underwent oocyte retrieval twice in one cycle, and the numbers of retrieved oocytes and transferable embryos from the luteal phase were significantly higher than those from the follicular phase in the same menstrual cycle. Conclusions: Compared with the GnRH-ant protocol, the LPOS protocol may be a better regime for PORs that can increase the numbers of retrieved oocytes and transferable embryos as well as the pregnancy rate.